The Impact of Work Hours and Cultural Expectations on Mental Health in Japan - Haga, Tatsuhiro; Tanaka, Hiroshi; Fujiwara, Kei; Suzuki, Yuki; Matsumoto, Yoshiko (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study examines the relationship between Japan's work culture and the mental health of its workers, focusing on stress, anxiety, and depression caused by long working hours and high productivity demands. Japan’s work culture, which emphasizes loyalty to the company and endurance, has contributed to a significant rise in mental health issues. Despite efforts by the government and companies to reduce overtime and provide mental health support, the policies implemented so far have proven insufficient in addressing the root causes of workplace stress. This research incorporates in-depth interviews, surveys, and case studies from workers across both private and public sectors. The findings indicate a strong correlation between long working hours and elevated stress levels, with workers in the private sector, younger employees, and women experiencing higher levels of anxiety and stress. Policies like flexible work hours, mental health programs, and reduced overtime showed positive impacts on well-being, but their inconsistent implementation limits their effectiveness. The study concludes that policies must go beyond reducing working hours and incorporate structural changes in workplace culture. Future research should investigate the long-term effects of these reforms, explore sector-specific mental health needs, and consider gendered aspects of work-related stress.